Cognitive Assessment in Learning Midwife Care (ASKEB I) by Midwifery Students of STIKES Maranatha Kupang - Rosina Kardina Kidi Hurek (UHAMKA Press, 2018)
P Cognitive Assessment is an assessment of learning efforts based on the results of one’s comprehension. One of the factors that affect the result of one’s learning is the media and interest. The objective of this study is to find out the effects of presentation slide, demonstration, video and interest of learning ASKEB I. They affect toward the Cognitive Assessment by Midwifery students semester IV in STIKES Maranatha Kupang, 2016. This study is using cross sectional method with quantitative approach. 120 respondents taken using total sampling method. Analysis method applied in this study is Structural Equation Modelling (SEM) method using SmartPLS 2.0 dan SPSS 18. The results of hypothesis test show variables that directly affect the cognitive assessment. (42.47% towards the learning media and 28.68% towards the learning interest). On the other hand, there is 4.05% variable found, affecting the learning media in cognitive assessment via learning interest. The Q-Square test results showing the analysis model conducted in this study is able to explain 87.48% of the phenomenon researched. The 12.51% rest is the factors that are not taken in this research. This is showing that there is correlation between learning media and learning interest toward cognitive assessment. It is expected that all the parties increase the learning interest and update more variable learning media to get good achievement.